ESTIMATION OF GENETIC PARAMETERS, CORRELATION, AND GENETIC RELATIONSHIP OF TOMATOES GENOTYPE IN LOWLAND - Marlina Mustafa; Muhamad Syukur; Surjono Hadi Sutjahjo; Sobir Sobir (Agrotech Journal, 2016)
The cultivation of tomato in lowland experience many obstacles, such as low produvtivity. One effort to increase tomato productivity  in lowland is through selection of tomato genotype for high yield and yield component  in lowland. This study aims to determine the variability based on genetic information, heritability and correlation of characters as well as the yield components of tomato genotypes relationship patterns in the lowlands. A Randomized Complete Block Design was used to characterization base on best genotype of yield component character, genetic variability, broad sense heribility and correlation to yield. Genotype of tomato tested had diverse characteristics. Best genotypes based on the yield character is IPB T1, based on the number of fruit per plant is IPBT30, based on the fruit length and day to flowering is IPB T74, based on the fruit diameter is IPB T73 and fruit thickness is IPBT60. Wide genetic diversity has a high heritability. Number of fruit per plant, fruit length, fruit diameter, and fruit thickness has a wide genetic diversity and high heritability. Yield characters has a narrow genetic diversity and heritability is low. Characters that have a direct impact on the yield are the fruit diameter. Based on the cluster analysis, tomato genotypes are grouped into five groups. Group I consists of seven genotypes (IPBT1, IPBT58, IPBT60, IPBT64, IPBT78, IPBT80 and IPBT82), group II consists of one genotype (IPBT74), group III consists of three genotypes (IPB T13, IPB T73 and IPB T86), group IV consists of five genotypes (IPBT3, IPBT33, IPBT43, IPBT53, and IPBT3) which is characterized by fruit thickness, fruit length and days to flowering, and group V consists of one genotype (IPBT30).